(untitled) (Innovative professional education, 2022)
The relevance of the use of interactive learning methods in the educational process of professional (vocational and technical) education institutions in order to prepare future qualified workers for employment through self-employment is substantiated. The interactive methods that are most effective in the process of developing the skills of students, important for building a professional career, in particular in the field of small business, are characterized.